Pelatihan Strategi Penulisan Artikel Ilmiah untuk Publikasi di Jurnal Internasional Bereputasi Tinggi bagi Periset BRIN - Pamungkas, Onok Yayang (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The problem that underlies this PkM activity is the lack of optimal competence of BRIN researchers in writing scientific articles for publication in reputable international journals. For this reason, this PkM activity aims to provide training on strategies for writing scientific articles for publication in reputable international journals. The method used is in the form of training and mentoring for BRIN researchers. The training is carried out online (online) through the zoom application, while discussions and consultations (assistance) are also carried out online through the Whatsapp application. This activity is carried out in four stages, including; preparation stage, implementation stage, discussion and consultation stage, and evaluation stage. Based on the results and discussion, it is shown that the trainees still experience problems in publishing scientific articles. Based on discussions and consultations, participants have high enthusiasm to be able to carry out quality research and publish in reputable international journals. Through this PkM activity, it is hoped that it will increase the capacity of BRIN researchers in writing quality scientific articles for international publications.. Keywords: publication strategy, scientific articles, community service